Strengths of associations between depressive symptoms and loneliness, perfectionistic concerns, risky alcohol use and physical activity across levels of sleep quality in Swedish university students: A cross‐sectional study. (11th October 2022) - Johansson, Fred; Côté, Pierre; Onell, Clara; Källberg, Henrik; Sundberg, Tobias; Edlund, Klara; Skillgate, Eva
Summary: Previous research shows that sleep quality may interact with some other predictors of depression, such that poor sleep could strengthen the association between these factors and depression. We aimed to determine the presence of statistical interactions between sleep quality and loneliness, risky alcohol use, perfectionistic concerns and/or physical inactivity in relation to depressive symptoms. Further, we aimed to describe the functional form of the statistical interactions and associations. We used a cross‐sectional design and included 4262 Swedish university students. All measures were self‐reported, sleep quality was measured with the Pittsburgh Sleep Quality Index, and depressive symptoms with the short‐form Depression, Anxiety and Stress Scale. Regression models of increasing complexity (linear and non‐linear, with and without interactions) were compared to determine the presence of associations and statistical interactions, and to explore the best functional form for these associations and interactions. Out‐of‐sample R 2 from repeated cross‐validation was used to select the final models. We found that sleep quality was associated with depressive symptoms in all final models. Sleep quality showed a linear interaction with perfectionistic concerns in relation to depressive symptoms, such that perfectionistic concerns were more strongly associated with depressive symptoms when sleep quality was poor. Loneliness, risky alcohol use and physical inactivity were non‐linearly associated with depressive symptoms but did not interact with sleep quality. We concluded that out of the four examined variables, only perfectionistic concerns interacted with sleep quality in relation to depressive symptoms. This interaction was weak and explained little of the overall variance in depressive symptoms.